The relationship between total quality management practices and individual readiness for change at petroleum exploration and production authority in Yemen - Al-Maamari, Qais Ahmed; Abdulrab, Mohammed; Al-Jamrh, Bassam Ali; Al-Harasi, Abdo Hasan (American Association for Science and Technology, 2017)
The focusing of the Total quality management practices is the most important for any organization to increasing level of individual readiness for change regarding TQM implementation, and improve efficiency as well as productivity, a result of that lead to improve performance in all. The total quality management in organizations in Yemen still a lack with issues in implementation of TQM. In this research is aimed to attempt to significant attention on the most important factors that foster the success of change initiative such as TQM implementation at Oil Units in Yemen. The study examines the association between total quality management practices (Human resource management, process management, customer focus & satisfaction, top management commitment, supplier partnership and learning & Training) with individual readiness for change for TQM implementation. This article is focusing on critical success factors who are always association with TQM in work. The collected data analysis showed that three of TQM practices, such as Customer Focus & Satisfaction (CFS), Supplier Partnership (SP) and Human resource management (HRM) are the most supportive TQM practices for increasing IRFC regarding implementation of TQM. Consequently, in this study makes a unique contribution by providing an advanced and deeper comprehension of the relationship between TQM practices and IRFC for TQM implementation at Petroleum Exploration and Production Authority in Yemen.